INSTRUCTIONAL STRATEGIES FOR VOCABULARY TEACHING IN A FOREIGN LANGUAGE TO FOSTER COMMUNICATIVE COMPETENCE IN PUPILS FROM GRADES 1–4 - Ribinskaya Elvira Grigoryevna (Western European Studies, 2025)
This article investigates effective instructional strategies for teaching foreignlanguage (English) vocabulary to primary school pupils (grades 1–4), aiming to develop their communicative competence. Drawing on theoretical frameworks such as communicative competence (Dell Hymes; Michael Canale & Merrill Swain), child-centered pedagogy, and empirical studies on methods like Total Physical Response (TPR), songs & rhymes, and lexical-based instruction, the article analyzes how vocabulary instruction can be designed to support interactive, meaningful language use rather than rote memorization. The article concludes that a combination of multimodal, interactive, context-rich, and developmentally appropriate strategies significantly enhances young learners’ vocabulary acquisition, motivation, and communicative competence
Keywords: vocabulary teaching; communicative competence; young learners